Metode Pengembangan Materi Ajar Bahasa Arab yang Inovatif - N, Nurfika; Hamzah, Andi Abdul (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The purpose of this study was to find out how to develop teaching materials based on a project-based approach, to find out the use of creative and interactive media, and to find out creative learning techniques. This study was conducted using the library research method, by taking data sources from previous studies, books, magazines, and others. The results of this study indicate that the innovative Arabic language teaching material development method is expected to be able to improve the quality of students' language through easy, creative and interactive techniques and strategies through project-based learning, through media such as audio, video and other multimedia and through game strategies.